DESAIN SARANA BAWA ALAT PERKEBUNAN - Dita Andansari; Suharbianto . (Indonesian Society of Applied Science, 2018)
ABSTRACTGardening is an activity cultural ancestors which has been passed down from generation to generation that is on the face of this earth until humans are present. Gardening can not only be done on vast land but also in the yard of the house. The large number of garden tools such as sputters, chainsaws, sekateur, hand scrapers, hand forks, and machetes. carrying a special bag to make things easier bring the equipment is before the equipment is only placed in a backpack along with other equipment, so it must be unpacked when the equipment will be used. then often every time using gardening tools but after wearing it we sometimes forget to put and left behind after being used to scattered and cluttered everywhere.Therefore it is necessary to create special means to carry and tidy up the plantation equipment. The design method used is collecting data, analyze the data, determine the design concept, create alternative design, developing alternative designs, to final design. To that end, with the